Evaluation Of Bone Mineral Density Among Patients With Depression In Penang Island, Malaysia - Kurmanji, Jaafer Mosadek (2009)

(untitled)
Depression a mental illness described by sadness, loss of interest, troubled sleep and appetite and low energy levels. It is also correlating with some alterations in endogenous hormonal levels as well as poor socio behaviors, resulting in modification in a bone metabolism and bone remodeling process. Studies have shown that there is a significant association between depression and low Bone Mineral Density (BMD) and this prompt the effort to evaluate this relationship in a Malaysian population in Penang, Malaysia.